Analisis Perilaku Kerja Prestatif dalam Perspektif Al-Qur'an - Waryainah, Waryainah (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Achievement Work Behavior is one of the work attitudes that need to be applied by workers, namely where a worker always has the ambition to move forward (ambition drive). Whereas in the Qur'an Allah has arranged all human affairs in such a way as to serve as a guideline as well as regarding achievement work behavior. This is what became interesting until the author took the title of the research "Achievable Work Behavior in the Perspective of the Qur'an'' with the formulation of the problem: how does the Qur'an explain about achievement work behavior and how it correlates with achievement work behavior in general. The aim is to find out how the views of the Qur'an on achievement work behavior and to find out its correlation with achievement work behavior in general. In his interpretation, the writer uses the Maudhu'i interpretation method. By collecting several verses that contain content about achievement work behavior. While in writing this thesis the author uses several research methods, Library Research or library research with data sources used, namely primary data sources and secondary data sources. The results of this study indicate that Achievement Work Behavior is relevant to what the Qur'an wants and even recommended by the Qur'an but more broadly the Qur'an explains that the main goal of every work done is to return to Allah SWT also in al-Qur'an. -The Qur'an sees the impact of this achievement work behavior on human beings and their surroundings, not only in terms of material.